Uncertainty Analysis of Decay Heat Power after Fast Neutron Fission Based on Sensitivity/Uncertainty Method - WANG Fenglong1, YANG yong1, , HUANG Xiaolong2 (Yuanzineng kexue jishu)
To deal with the problem that notable light water reactor decay heat calculation standard is not suitable for fast reactor, this paper adopted the sensitivity/uncertainty (S/U) method to analyze the uncertainty introduced by nuclear data in the calculation of decay heat. Calculation method of decay heat uncertainty of fast neutron fission was studied. The uncertainty of decay heat of fast neutron fission for 235U and 239Pu in 1-1013 s after reactor shutdown, and its relationship with the uncertainty of half-life, energy, fission yield, and branching ratio, were calculated. On this basis, Python programming language was used to develop a set of analysis software for evaluating the uncertainty of decay heat. According to the decay heat of fission products of 235U and 239Pu after fast neutron fission, the standard uncertainty data with reference value were obtained. The results show that the uncertainty of decay heat of fast neutron fission for 235U and 239Pu ranges from 2% to 10% in 1-103 s and 108-1010 s. The uncertainty of decay heat of fast neutron fission in 103-108 s is less than 2%. The calculation process for analyzing the uncertainty of decay heat after fast neutron fission for 235U and 239Pu established in this paper can be used in the subsequent uncertainty analysis and evaluation of decay heat in sodium cooled fast reactors, lead cooled fast reactors, and gas cooled fast reactors.